Dermoscopic assessment of skin toxicities in patients with melanoma during treatment with vemurafenib - Rajczykowski, Marcin; Kaminska-Winciorek, Grazyna; Nowara, Elzbieta; Samborska-Plewicka, Marzenna; Giebel, Sebastian (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Introduction : The use of vemurafenib in melanoma has improved the survival of patients; however, it is associated with skin toxicities. Aim : To assess skin toxicities by dermoscopy in patients treated with vemurafenib. Material and methods : Eight patients with BRAF V600 mutation positive metastatic melanoma were examined dermoscopically during vemurafenib treatment. All skin lesions occurring during therapy were assessed clinically and dermoscopically using a hand-held dermoscope with polarised and non-polarised light. Skin lesions suspected for malignancy appearing during therapy were totally surgically excised with consecutive histopathological examination. Results : All 8 examined patients developed skin toxicity. The majority of patients (7/8) presented G1 skin toxicity according to CTCAE version 4.3. Only 1 of them had G2 skin toxicity. The most common dermoscopy findings in our study were hyperkeratotic verrucas in 5 patients (5/8) with structureless pattern. In some of them we also observed central dots, exophytic proliferation, hairpin vessels and homogeneous haemorrhage. Other findings were hyperkeratosis of the nipples (5/8) with brownish to yellowish, angular clods with a tendency to be more confluent in dermoscopy. Palmar plantar erythrodysaesthesia (3/8) showed dermoscopically a yellowish, homogeneous pattern. Four melanocytic skin lesions in 2 patients were surgically excised due to suspected malignant transformation. In most of them we observed an atypical pigmented network (abrupt cut-off, big holes), atypical globules and a homogeneous blue pattern; however, histopathological diagnosis excluded any malignancy. Conclusions : Dermoscopy seems to be an easily performed and valuable method for assessment of skin toxicities during oncological therapy, at any time of the treatment.